INOVASI OLAHAN PANGAN HASIL PERTANIAN SEBAGAI PEMBERDAYAAN WANITA DAN PENGEMBANGAN EKONOMI KELUARGA MELALUI PROGRAM UP2K PKK DESA PONDOKKELOR - Tyas, Esti Alfianing; Latifa, Dona; Christanty, Merry (Kalam Nusantara Institute, 2024)
Women's empowerment and family economic development are important issues in improving community welfare. This research explores various innovations that can be applied to empower women and promote family economic growth. Using qualitative and quantitative approaches, this research identifies innovative methods such as skills training programs, access to technology, and microfinance that can strengthen the role of women in the family economy. An analysis of several successful cases from different regions shows that a combination of educational support, market access, and technology utilization can significantly improve women's economic independence. The results suggest policies and strategies that can be adopted by the government and private institutions to expand the positive impact of these innovations. This research is expected to provide insights for decision makers in designing more effective and sustainable empowerment programs.